Massive low digestive hemorrhages - Asiner, Boris (Cirugía del Uruguay, 1977)
Reference to massive low digestive hemorrhages is scarce. In· 25 years of urgency surgery the author created 32 cases involving this serious complication, which he reports and analyzes. Topographically, the highest incidence was in the colon -20 cases- where 18 such hemorrhages were caused by "diverticulosis". Most of them